2019
DOI: 10.1001/jamanetworkopen.2019.13818
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Multimodal Educational Intervention for Primary Care Physicians With Prescriptions of Buprenorphine for Opioid Use Disorders

Abstract: This quality improvement study examines the association of a multimodal educational intervention for primary care physicians (PCPs) with prescriptions of buprenorphine for treatment of patients with opioid use disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…Three interventions measured the impact of AD on knowledge of opioid prescribing, the prescription monitoring programme (PMP) and opioid use disorder (OUD) treatment. 18 , 26 , 29 Kattan et al used verbal pre–postintervention provider surveys to assess knowledge related to opioid treatment of non-cancer pain. 26 The authors found that after the AD intervention, there were statistically significant increases in correct responses ( p <0.01) for each of the three survey questions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three interventions measured the impact of AD on knowledge of opioid prescribing, the prescription monitoring programme (PMP) and opioid use disorder (OUD) treatment. 18 , 26 , 29 Kattan et al used verbal pre–postintervention provider surveys to assess knowledge related to opioid treatment of non-cancer pain. 26 The authors found that after the AD intervention, there were statistically significant increases in correct responses ( p <0.01) for each of the three survey questions.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a study by Clark et al initially assessed provider knowledge, beliefs and barriers to the buprenorphine prescribing process. 29 The top concerns of physicians were challenges around the treatment of OUD patients, limited outpatient counselling options for substance use, the time needed to manage OUD patients and insufficient personal knowledge about prescribing buprenorphine. After the multifaceted intervention with AD, there was an increase in buprenorphine prescribers and patients receiving OUD treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Shown here is the proportion of nonwaivered respondents who perceived buprenorphine to be not at all beneficial, not that beneficial, somewhat beneficial, or very beneficial for their patient populations, and the proportion of providers who expressed no interest, slight interest, moderate interest, and high interest in buprenorphine prescribing. PCPs in the past, 22,23 but they have not traditionally focused on the benefits of buprenorphine therapy for providers' specific patient populations. Interventions that highlight the impact of buprenorphine treatment on providers' patient panels may increase the efficacy of preexisting educational programs and decrease the discrepancy between patients' needs for buprenorphine and providers' ability to prescribe.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggested that PCPs lack a full understanding of unnecessary drugs and ignore their non-health related impacts, such as wasting medical resources. Education is an important priority to help PCPs prescribe wisely [ 31 ]. A systematic review implied that the prescribing behaviors of PCPs could be successfully changed through academic detailing [ 32 ].…”
Section: Discussionmentioning
confidence: 99%